2019
DOI: 10.1016/j.heliyon.2019.e02868
|View full text |Cite
|
Sign up to set email alerts
|

A chronic high-fat diet causes sperm head alterations in C57BL/6J mice

Abstract: A chronic-positive energetic balance has been directly correlated with infertility in men, but the involved mechanisms remain unknown. Herein we investigated weather in a mouse model a chronic feeding with a diet supplemented with chicken fat affects sperm head morphology. To accomplish this, we fed mice for 16 weeks with either control food (low-fat diet, LFD) or control food supplemented with 22% chicken fat (high-fat diet, HFD). At the end of the feeding regimen, we measured: redox and inflammatory changes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Despite the essential role of cholesterol during spermatogenesis, hypercholesterolemia mediated excessive cholesterol accumulation negatively alters male reproductive functions, including sperm maturity, viability and fertilization. These alterations might be associated with the oxidation of various compenents in diet, particularly lipids 29 . Regarding the present study, observation of increased cholesterol and MDA levels in testes tissue reflects the role of hypercholesterolemia mediated lipid oxidation in testicular damage.…”
Section: Discussionsupporting
confidence: 54%
“…Despite the essential role of cholesterol during spermatogenesis, hypercholesterolemia mediated excessive cholesterol accumulation negatively alters male reproductive functions, including sperm maturity, viability and fertilization. These alterations might be associated with the oxidation of various compenents in diet, particularly lipids 29 . Regarding the present study, observation of increased cholesterol and MDA levels in testes tissue reflects the role of hypercholesterolemia mediated lipid oxidation in testicular damage.…”
Section: Discussionsupporting
confidence: 54%
“…As well as, Barth et al (2010) suggested that the prolonged HFD may lead to accumulation of lipids within mitochondria triggering mitochondrial autophagy or the mitophagy process. Moreover, Funes et al (2019); Ashrafi et al (2013) found several structural alterations in testicular tissues of hypercholesteremic animals and attributed these changes to reactive oxygen species and increase oxidative stress which are extremely cytotoxic to the spermatozoa and may play a critical role in the accumulation of cholesterol in the testicular tissue, as well as cytoskeleton disorganization during spermiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…(2010) suggested that the prolonged HFD may lead to accumulation of lipids within mitochondria triggering mitochondrial autophagy or the mitophagy process. Moreover, Funes et al. (2019) ; Ashrafi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They discovered that honey escalates the activities of sorbitol dehydrogenase, a testicular marker enzyme involved in spermatogenesis by 31% [32]. Besides that, honey also has been shown to improve the ability to get and sustain a penile erection [33]. Therefore, it can be concluded that all these mechanisms are responsible for reducing spermatozoa damage and dysfunction, thus improving the sperm parameters.…”
Section: Discussionmentioning
confidence: 99%